Heat transfer with viscous dissipation and entropy generation in a nanofluid flow through a porous medium - Swain, Bharat Keshari; Sahu, Sipun; Ojha, K. L.; Dash, G.C. (Journal of Naval Architecture and Marine Engineering, 2023)
This article describes the Al2O3/Cu/Ag-H2O nanofluid stagnation-point flow through a porous medium with emphasis on heat transfer as well as magnetohydrodynamic (MHD) behavior and entropy generation. The main motivation is to do the MHD flow of nanofluid and look into the repercussions of viscous dissipation, which has many applications in various industries, especially the extrusion process where the durability of the end product is of interest. The governing equations are solved using similarity transformations and DTM-Padé approximations, and the solutions are then compared to the outcomes of the numerical technique (shooting technique and Runge-Kutta 4th order method), which validates the accuracy of the research. Some important findings are: entropy generation is to decrease for higher values of Br in a streamline manner within asymptotic pattern; viscous heating is dominant in the neighborhood of the plate for higher value of Br and for small values the distribution is smooth across the flow field; decrease in entropy generation for higher value of Br shows that there is a base value or residue left over energy in the process of entropy generation, which is important in its own revelation and application basis. Journal of Naval Architecture and Marine Engineering, December, 2023, P: 127-142